Building a systems thinking prevention workforce. (14th February 2020) - Bensberg, Monica; Allender, Steven; Sacks, Gary
Abstract: Issue addressed: Healthy Together Victoria (HTV) was a large‐scale intervention that adopted a systems approach to prevention. It established the capability of an inexperienced workforce by cultivating their understanding of systems theories, tools and practice. This paper explores how this capacity was developed and what helped and hindered the process. Methods: This qualitative research included 31 primary semi‐structured interviews that focused on participants' understanding of systems thinking. Deductive thematic analysis was undertaken. A workforce development framework informed the coding that was used to create a causal loop diagram. Results: The findings display the multiple influencers on capacity‐building. Practice change was enabled with training—although it lacked coordination and participation was limited. Yet, the systems approach was strengthened with governance arrangements, policies, funding, team support and leadership that empowered practitioners to trial systems methods. Capacity‐building was hindered by HTV's unspecified theory that made it harder for novice practitioners to grasp. Funding cuts due to political changes reduced the initiative's duration and prompted resignations, causing the newfound experience to exit the workforce. Conclusion: Capacity‐building for systems practice requires a holistic approach of simultaneous, complimentary actions that address the individual and environmental influences of workforce development, especially the drivers of organisational culture that facilitate new practice. So what?: Effective training methods should specifically teach skills and knowledge that help practitioners to implement systems thinking. The workforce development requirements of other contributors also need to be considered, in addition to the policies, opportunities and resources that embed practice change.